Determination of Aggregation Numbers of Bile Salt Micelles with the Depression of the Solution Freezing Point - Poša, Mihalj; Popovic, Kosta (Journal of Applied Solution Chemistry and Modeling, 2013)
The special geometry of the steroid skeleton causes formation of bile acid anion micelles with small aggregation numbers, in contrast to aliphatic amphiphiles. Relative to the tendency to reduce membrane toxicity, pharmacological investigations of bile acids are mainly concerned with their oxo derivatives. Since micelles of these bile acids have been insufficiently studied, the objective of this work is the determination of aggregation numbers of corresponding micelle monomers. The aggregation numbers were determined using the freezing point depression of the solutions by applying the appropriate equations of Debye-Hückel, Guggenheim and Gibbs-Duhems, and using pNa data measured with a Na-selective electrode. Depending on the structure of the bile acid anion, the values obtained for the aggregation numbers were in the range from 2.09 to 3.44. The increase in number of oxo groups in the molecule is accompanied by a decrease in hydrophobicity of the convex side of the steroid skeleton of the bile acid anion, resulting in a lower aggregation number.